2012
DOI: 10.3748/wjg.v18.i10.1048
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous injection of mesenchymal stem cells is effective in treating liver fibrosis

Abstract: MSC administration is able to protect against liver fibrosis. Intravenous injection is the most favorable treatment modality through promotion of IL10 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
91
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(102 citation statements)
references
References 39 publications
8
91
0
1
Order By: Relevance
“…19 Furthermore, several animal studies determined that the administration of mesenchymal-derived stem cells significantly reduced fibrosis in the lung, kidney, and liver. [12][13][14] There are, however, no reports of stem cell-based therapy in the clinical management of urethral stricture disease. Our study is a proofof-concept study that demonstrates that local injection of ADSCs prevents fibrosis induced by TGF-β1 injection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Furthermore, several animal studies determined that the administration of mesenchymal-derived stem cells significantly reduced fibrosis in the lung, kidney, and liver. [12][13][14] There are, however, no reports of stem cell-based therapy in the clinical management of urethral stricture disease. Our study is a proofof-concept study that demonstrates that local injection of ADSCs prevents fibrosis induced by TGF-β1 injection.…”
Section: Discussionmentioning
confidence: 99%
“…11 Furthermore, a number of animal studies have demonstrated that mesenchymal stem cells have antifibrotic properties that can reduce fibrosis in the lung, kidney, and liver. [12][13][14] We sought to evaluate the potential therapeutic benefits of adipose-derived stem cell (ADSCs) therapy in decreasing fibrotic tissue in a rat model of urethral fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…We identified eGFP DNA in the lungs and liver after systemic infusion of FVB-GFP MSCs to mice with and without arthritis. MSCs have been shown to engraft to lung and liver and this is to be expected due to the high circulating blood volume in these organs [48][49][50]. During active inflammation, hepatocytes become upregulated and increase production of acute phase proteins [51] leading to the hypothesis that the increased hepatocyte activity may generate chemoattractants for MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Carboxy fluorescein diacetate succinimidyl ester (CFSE) 39 and 4,6-diamidino-2-phenylindole, dihydrochloride (DAPI), 24 chloromethylbenzamidodialkylcarbocyanine (CM-Dil) 40 fluorescent dyes are commonly used to examine cell localization. The red fluorochrome PKH26, which mainly binds to the cell membrane, is an efficient cell tracer to locate transplanted cells.…”
Section: Tracing Of Transplanted Cellsmentioning
confidence: 99%
“…17 Injection of doses between 0.5-1 mL/kg CCl4 dissolved in olive [18][19][20] or corn oil 5,21 twice a week for 4-8 weeks 18,22 have been used for liver injury in small animal models. 12,20 CCl4 can be injected to rodents intraperitoneally 12,23,24 or subcutaneously. 5,18,20,21 Paracetamol, 25 ally alcohol (AA) 26 and dimethylnitroseamine (DMN) are other chemical agents for inducing liver damage in rodents.…”
Section: Introductionmentioning
confidence: 99%